Jumlah dan Distribusi Stomata pada Daun Beberapa Spesies Tanaman Dikotil dan Monokotil - Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The aim of research was to infestigate amount and distribution leaf stomata Dicotyledoneae and Monocotyledoneae. This research was classification amount study of stomata, until can know estimate transpiration at leaf plant. One thousand species was use to research instead of 68 Dicotiledoneae and 32 Monocotyledoneae. Preparation of stomata with replication methode. Research parameters was amount and distribution of leaf stomata, further more data classification in catagorizing few to not limited. Result of this reseach showed that few catagory amount stomata was reach 24% , enough 20%, much 19%, verymuch 14% and 23% not limit catagory. Distribution spread stomata was reach 68% ( water jasmine axcept) and parallel stomata was reach 32%